Research on an Ice-Breaking Mechanism Using Subglacial Resonance - Zegang Tian; Zixu Zhu; Bo Tong; Nianming Hu; Mingyong Hu; Yongbao Liu (Journal of Marine Science and Engineering)
The Arctic ice layer serves as an excellent cover for strategic nuclear submarine forces, but it also poses significant challenges when submarines surface. This paper proposes a method for breaking through the ice layer and surfacing in polar environments based on the principle of resonance. This method eliminates the need for direct contact between the submarine and the ice layer, solving the current issues with submarine ice-breaking methods that demand high strength from the submarine and pose risks to both the submarine and its crew. Through theoretical analysis, numerical simulation and experimental verification, the vibration characteristics and fracture mechanism of the ice layer under the action of excitation loads were studied. Experiments showed that when the excitation frequency matched the fundamental eigenfrequency Ω1 of the ice layer, obvious resonance occurred and cracks appeared in the ice layer. A dynamic model of the ice layer was established using Abaqus software, and modal extraction and stress analysis were carried out. The error between the Ω1 obtained by numerical simulation and the experimental results was only 0.53%, verifying the reliability of the model. After applying the excitation load with a frequency of Ω1, the stress in the ice layer gradually expanded to the strength limit of the ice, achieving an ice-breaking effect consistent with the experimental results. Experimental and simulation results showed that the use of Ω1 for resonance ice-breaking had the best effect. When the ice layer resonated, the stress increased first and then stabilized, and cracks occurred before the stress stabilized to achieve the ice-breaking effect.